2007
DOI: 10.1016/j.jri.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of IFN-α/β signaling in the prevention of genital herpes virus type 2 infection

Abstract: Genital herpes, caused by herpes simplex virus type 2 (HSV-2), is the most common genital ulcer disease worldwide. HSV-2 infection causes a variety of symptoms, ranging from subclinical/silent infection to severe and recurrent episodes of genital blisters and ulcers, and the virus can also in rare cases cause meningitis. In primary infection, the virus sequentially enters and replicates in epithelial cells followed by local sensory neurons. In the latter, a life-long infection is established via the induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 148 publications
4
44
0
1
Order By: Relevance
“…Thus, poly(I:C) might have most potential as a topical strategy that could be applied immediately within 24 h after exposure to curb local spread. In addition, the ability of TLR3 ligation to limit herpes simplex virus infection (4,28,33,63,76) would also help to control the spread of HIV (11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, poly(I:C) might have most potential as a topical strategy that could be applied immediately within 24 h after exposure to curb local spread. In addition, the ability of TLR3 ligation to limit herpes simplex virus infection (4,28,33,63,76) would also help to control the spread of HIV (11).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic CpG-containing oligonucleotides that activate TLRs have been experimentally used to induce an antiviral state following vaginal instillation (5,21,52). Central to the antiviral effect of TLR ligands is the production of IFN-␣ by plasmacytoid dendritic cells (pDCs) (34,55). The importance of type I IFNs in resistance to HSV-2 infection is also suggested by the fact that topical application of IFN-␣1-expressing plasmids to the vaginal epithelium increases the resistance of mice to HSV-2 challenge and spread (26).…”
mentioning
confidence: 99%
“…pDCs deficient in TLR9 are unable to produce IFN−α upon HSV-2 stimulation [72,73] and, in vivo, TLR9-/-mice infected with HSV-2 have no detectable circulating IFN−α resulting in the rapid pathology and reduced survival of these mice [74,75]. Consistent with the importance of type I IFNs in the anti-HSV response, IFNAR1-/-mice have increased susceptibility to HSV-2 infection, with elevated viral replication [76]. Similarly, STAT1-/-mice demonstrate increased HSV-1 replication in the cornea [77].…”
Section: Ifns and Hsvsmentioning
confidence: 87%
“…Mouse models have demonstrated that TLR agonists can provide protective immunity in vaccination against HSV infection [95,96] through induction of IFN signaling pathways [76]. With vaginal administration of the TLR9 ligand, CpG oligodeoxynucleotide, mice were protected from a HSV-2 vaginal infection [75,97]; however, the mechanism for protection was unclear.…”
Section: Ifns and Hsvsmentioning
confidence: 99%
See 1 more Smart Citation